Capital Structure Analysis: Key Financial Indicators in Manufacturing - Sianturi, Antar MT; Siahaan, Magda; Pradipta, Arya (Journal of International Accounting, Taxation and Information Systems, 2024)
This study focuses on how liquidity, asset composition, free cash flow, and profitability impact capital structure.   It also explores how profitability can affect the relationship between liquidity, asset composition, and free cash flow with capital structure. The study focused on collecting information from 50 manufacturing firms that are publicly traded on the Indonesia Stock Exchange over a period of three years, totaling 121 data points. The data analysis method uses multiple linear regression with the help of the Statistical Package for Social Sciences program. The study's findings suggest that there is some evidence to support the idea that liquidity has a negative impact on capital structure. The asset structure variable and the free cash flow variable do not affect capital structure. The profitability variable is proven to strengthen the negative effect of liquidity on capital structure. Nevertheless, it is unable to enhance the favorable impact of the composition of assets and the detrimental impact of surplus cash flow on the firm's financial structure. According to the research, it is suggested that the board members and executives of the organization should be responsible for optimizing resources and driving up the company's earnings; investors who want to invest in manufacturing companies should do an investment assessment.